Pernikahan Syarifah dengan Non-Sayyid di Patokan Kraksaan Probolinggo Perspektif Imam Malik dan Imam Syafi’i - Masruroh (State Islamic University (UIN) of Sunan Ampel, 2014)
This article focuses on sharifah marriage with non sayyid man in village Patokan, Kraksaan, Probolinggo within the perspective of Imam Malik and Imam Shafi’i. In this village, there are two cases of marriage between sharifah and non sayyid. First, the marriage between sharifah and non sayyid implemented with the consent and approval of her guardian. Second, the marriage between sharifah and non sayyid conducted without the permission and consent of her guardian, the sharifah is married by a judge guardian. Imam Malik and Imam Shafi’i view that the sharifah marriage with non sayyid man which carried out on the guardian’s permission is valid. The marriage conducted without the consent of the sharifah’s guardian, according to Imam Malik, is legitimate. Meanwhile, according to Imam Shafi’i, the marriage is null and void for lack of willingness of the guardian. Apart from the Priest’s opinions, in practice, the marriage between sharifah and non sayyid is being happy.